Bactrial flora of Yaks (Poephagus grunniens) - SASMAL, DEVASIS; BANDYOPADHYA, SAMIRAN; GHOSH, MONOJ K; KONWAR, PAHARI; BORAH, BINGD D; BISWAS, TAPAS K; SARKAR, MIHIR (The Indian Journal of Animal Sciences, 2011)
The bacterial t10ra of 20 normal, 22 diseased and 7 dead yaks of varying age groups (2 months to 3.5 years) from Arunachal Pradesh were studied. Out of 135 isolates from the nonnal yaks'l 11 different species and unidentified groups of bacterial Â±lora were identified.Â